Near‐Infrared‐Absorbing Diketopyrrolopyrrole‐Based Semiconducting Polymer Nanoparticles for Photothermal Therapy. (13th February 2020) - Wei, Zuwu; Zhu, Bili; Cai, Yang; Yan, Dan; Lou, Yuheng; Guo, Zhiyong; Deng, Ping
Abstract: Photothermal therapy, an excellent therapeutic approach, has received much attention in recent years. Herein, a novel diketopyrrolopyrrole polymer (DPP‐BDP) is prepared, which shows intense near‐infrared (NIR) optical absorption and admirable photothermal conversion efficacy. Impressively, after assembly into nanoparticles (DB‐FA), the as‐prepared conjugated polymer demonstrates a uniformly distributed size around 200 nm with remarkable NIR absorption at 808 nm. Additionally, it displays high biocompatibility and photostability. More interestingly, the obtained DB‐FA NPs are uptaken by cancer cells and present excellent anticancer in vitro and in vivo under 0.8 W cm −2 or 1 W cm −2 NIR laser irradiation, respectively. Hence, this work is expected to pave the way for using conjugated‐polymer nanoparticles as a powerful photothermal agents for anticancer applications. Abstract : DB‐FA nanoparticles (NPs) demonstrate a uniformly distributed size around 200 nm, high colloidal and photostability, and excellent biocompatibility. Both in vitro and in vivo investigation reveals that the DB‐FA NPs possess high cancer cell killing ability and admirable tumor elimination efficiency (99.2%) under 808 nm laser irradiation. Therefore, the as‐prepared DB‐FA NPs hold great potential for photothermal therapy.